2017
DOI: 10.4103/1735-5362.202448
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathological effects of green tea nanoparticles in ironized mouse model

Abstract: Transfusion in the treatment of thalassemia gives rise to iron deposits in many organs. Since there are many obstacles in the use of deferoxamin (DFO) as an iron chelating agent, it is important to find another alternative therapy that can act as iron chelation. The study aims to compare the histopathological pictures of the heart and spleen in iron-induced rats after administration of DFO and nanoparticles of green tea extract. The research used experimental research design with a post-test only control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
3
3
0
Order By: Relevance
“…The decreased levels of hemoglobin might have resulted from the inability to utilize iron to make hemoglobin, as a result there was a decreased level of MCV due to small average RBCs size which might be a deficiency of iron, and this phenomenon is supported by mild to moderate hemosiderin deposit within the spleen of these groups. This has been reported in previous studies [48].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The decreased levels of hemoglobin might have resulted from the inability to utilize iron to make hemoglobin, as a result there was a decreased level of MCV due to small average RBCs size which might be a deficiency of iron, and this phenomenon is supported by mild to moderate hemosiderin deposit within the spleen of these groups. This has been reported in previous studies [48].…”
Section: Resultssupporting
confidence: 89%
“…5B) and sub-chronic (Fig. 5E) stages of the study suggests the destruction of defective or damaged red blood cells, as previously reported by other studies [47,48]. This could also be attributed to the cytotoxic effect of the major constituent of the LEO germacrene D [37].…”
Section: Resultssupporting
confidence: 85%
“…Optimal nanoparticle properties for pollution remediation include particles that are small, monodisperse, possess no particle–particle attraction, and do not passivate readily under aerobic and aqueous conditions . Our findings, along with other studies that utilize antioxidant rich green tea extracts to generate iron nanoparticles, have shown that high antioxidant concentrations lead to particles that agglomerate and form chainlike structures, thereby reducing the nanoparticle surface area available for remediative interactions.…”
Section: Results and Discussionsupporting
confidence: 58%
“…Sulistyo and colleagues (2017) observed that green tea nanoparticles have better effects in ironized mouse model thalassemia as compared to the green tea as a free compound. The green tea extract prepared into nanoparticles using chitosan as a carrier crosslinked with sodium tripolyphosphate (Sulistyo et al, 2017).…”
Section: Materials Active Compound Prediction Interaction Of Active Comentioning
confidence: 99%